Perencanaan Desain Renovasi Masjid Ahyani Thoriqul Jannah Tangerang Banten - Indah Yulia Sari; Andra Arie Anto; Karya Widyawati (Universitas Indraprasta PGRI, 2023)
Abstract This community service activity was carried out in the Tangerang sub-district. This Abdimas is a partnership program with cooperation partners Ahyani Thoriqul Jannah Masjid Prosperity Council (DKM) Mosque Tangerang Banten. The Ahyani Thoriqul Jannah Mosque, Tangerang, Banten is currently an old building which is feared to endanger the safety of the congregation/community who are carrying out worship. In addition, the capacity of the mosque is no longer sufficient to accommodate the Friday prayer congregation. Therefore, DKM Ahyani Thoriqul Jannah Tangerang Banten intends to completely renovate the mosque building with the principles of the congregation, by the congregation and for the congregation. DKM Ahyani Thoriqul Jannah Tangerang Banten faces a problem where there are no congregation members who are experts in their field. The team of community service lecturers at Indraprasta University PGRI offered DKM Ahyani Thoriqul Jannah Tangerang Banten a mutually beneficial partnership to carry out the renovation of the Ahyani Thoriqul Jannah mosque. DKM Ahyani Thoriqul Jannah resolved licensing issues, residents/congregants objected to mosque renovations and so on. While the team of community service lecturers at Indraprasta PGRI University prepared experts who would carry out tasks including pre-planning including reviewing the location of the mosque, land area, land form and soil structure, planning in the form of mosque architectural design and budget plans and participating in supervising the implementation of development from a technical point of view. Keywords: mosque design, mosque,